Analysis of Carbon Phase in Activated Coconut Shell Charcoal Based Teeth Whitening Using X-Ray Diffraction (XRD) Method - Alfira, Muna; Sumadiyasa, Made; Suarbawa, K. N.; Wendri, Nyoman (BULETIN FISIKA, 2024)
Now there are many teeth whitening products on the market which are claimed to be made from coconut shell charcoal. Charcoal in a material is in the form of carbon compounds, which can be in the form of graphene (GP), graphene oxide (GO) phases, and/or reduced graphene oxide (rGO). One method to identify the presence of the carbon phase is to use the X-Ray Diffraction (XRD) method. In this study, XRD characterization was carried out on one of the coconut shell charcoal-based tooth whiteners that has been registered with BPOM. Carbon phase analysis was carried out using software Match-3 and Origin 2019a. The results of the analysis showed that the tooth whitening samples contained carbon in the crystal phase of turbostratic graphite and amorphous reduced graphene oxide with a percentage content of 1.48% and 81.69%, respectively. The results also showed the presence of P, Al, and Si metal compounds.